Steel slag powder as supplementary cementitious material in UHPC: influence on key properties and microstructure - Qiao, Linbo; Zhou, Xiaoxi; Deng, Han; Du, Bind; Tang, Ruilin (Frontiers in Built Environment, 2025)
The large quantity of steel slag deposit has caused great environmental pressure. This study aims to recycle steel slag powder (SSP) as a supplementary cementitious material in the production of eco-friendly ultra-high performance concrete (UHPC) with varying SSP fineness (200–600 m2/kg) and dosage (20%–40%). The rheological properties, mechanical strength, autogenous/drying shrinkage, and microstructure of UHPC were systematically investigated using the Modified Andreasen and Andersen particle packing model. The results show that 20% SSP-400 optimally enhances compressive strength (133.5 MPa) by refining pore structure. SSP significantly mitigates autogenous shrinkage due to reduced self-desiccation, but increases drying shrinkage at high dosages/fineness (up to 21.5% at 40% SSP-600). Microstructural analysis confirms SSP-400 promotes complete hydration at 20%–30% dosage, while higher fineness accelerates early reactions but hinders later hydration. Ecological assessment validates SSP utilization reduces cement consumption and carbon footprint. Therefore, SSP-400 at 20% dosage enables sustainable UHPC with balanced performance.